VALUE ADDITION, PROFITABILITY, AND STRATEGIC DEVELOPMENT OF THE SOUTH SULAWESI SAGO AGRO-INDUSTRY - Muh Taufik; Andi Yulyani Fadwiwati; Muslimin; M Basir Nappu; Amiruddin Syam; Sahardi; Wardah Mustafa; Muh Asaad; Sri Bananiek Sugiman; Syuryawati; Herniwati; Ida Andriani; Rahmi Hanuddin; Maryam Nurdin; Arini Putri Hanifa (Gunung Djati Conference Series, 2026)
Sago is more than just a crop; it is a strategic asset for food security and a versatile industrial raw material. However, its true economic potential lies in agro-industrial transformation. This study examines how sago processing adds value and supports local livelihoods in North Luwu and Palopo, South Sulawesi. By combining the Hayami method for value-added analysis with partial budgeting and SWOT frameworks, we assessed the profitability of different processing stages and identified a path forward for the industry. Our findings reveal a sharp divide in economic outcomes. While wet and dry processing generate high value-added margins (over 40%), the milling stage remains below 15%. Interestingly, milling is actually the most efficient profit-maker, yielding a rate of 85.71%—far higher than drying or wet processing. This profitability extends to the people on the ground; with an R/C ratio of 1.6, sago processing is a highly viable business. However, a significant income gap persists, with loggers and processors earning roughly 25% more than the landowners who provide the raw material. To move the industry forward, the focus must shift toward farmer-led corporations and better land mapping. By establishing regional sago institutions and investing in infrastructure and human capital, South Sulawesi can move beyond basic milling into high-value derivative industries. These steps are essential to turning sago from a traditional staple into a modern industrial engine for the region.